Results of detection of yield, physical and chemical characteristics and freshness of the Mongolian mare milk - B, Sandagdorj; Ts, Baigalmaa; D, Purevsuren; S, Burenjargal; A, Gombojav; Ts, Urangoo; T, Enkh-Oyun; P, Nyam-Osor (Mongolian Journal of Agricultural Sciences, 2019)
To deepen understandings on changes in mare milk yield and composition along with lactation, physico-chemical characteristics and freshness of raw mare milk this study was conducted. The first trial on the change in mare milk yield and composition was conducted along with different lactation period using 7 adult mares. Milk yield was determined volumetrically after 2 hour foal separation. Hand milking with milk ejection by foal was applied. Milk yield reached at peak in August which corresponds to around 90th days of lactation. Lactose content reaches its max value at 90th day of lactation also and it remains as high as its peak until the milking season ends while the yield was decreased significantly (p≤0.05). Fat and protein contents were gradually decreased to the end of milking season. To conduct quality evaluation of raw mare milk it is vitally important to know physico-chemical characteristics. To clarify did this second trial in comparison with cow milk. Results were indicated that pH value is higher in mare milk and acidity and viscosity is lower in mare milk than those in cow milk. A hygienically obtained mare milk samples were used in this experiment. Acidity, pH and Total Bacterial Counts were monitored with the reference to raw horse milk standard of Mongolia. The results were indicated that hygienically obtained mare milk can be kept for 12 hours at room temp. In case of refrigerated condition it kept its acceptable freshness up 10 days of storage. Монгол гүүний саамны гарц, найрлага, физик-химийн шинж чанар, шинэлэг байдлыг тодорхойлсон дүн Хураангуй: Монгол гүүний саалийн хугацаанд (6-10-р саруудад) саамны гарц, найрлага түүний физик-химийн үзүүлэлт, хадгалалтын нөхцөл саамны шинэлэг байдалд хэрхэн нөлөөлөхийгтодорхойлох зорилгоор энэхүү судалгааны ажлыг хийж гүйцэтгэлээ. Судалгаанд 7-12 насны 7 гүүг ашиглав. Саамны гарц лактацийн 90 дэх хоногт хамгийн өндөр,120 болон 150 дах хоногуудад гарцын хэмжээ буурсан хэдий ч лактозын агууламж тогтворжиж байв. Физик-химийн зарим үзүүлэлтийг тодруулахын тулд үнээний сүүтэй харьцуулахад гүүний саам нь исгэлэн, рН, өнгө, урсанги чанар зэрэг үзүүлэлтүүдээр ялгаатай байв. Саамыг хадгалалтын хоёр өөр нөхцөл, хэмд хадгалж туршихад тасалгааны нөхцөлд 12 цаг хүртэл, хөргүүрийн нөхцөлд 10 хоног хүртэл шинэлэг байдал нь хадгалагдаж чадаж байлаа. Түлхүүр үг: Хадгалалт, саамны өнгө, саамны уураг, саамны лактоз